BIOLOGICALLY INSPIRED PROTOCOL FOR SECURING A CLASS OF NETWORKS - Yasir Abdelgadir , Mohamed; Azween, Abdullah (2010)
Although a lot of efforts have been made and a lot of studies have been carried out in networking security, we cannot go so far as to say the security requirements for the different types of networks are satisfied. As applications that are applicable to different networks mature, new security methods are considered necessary. Infrastructure-less environments are dynamic and mostly difficult to control; hence security methods designed for other types of networks might not be applicable. Mobile Ad hoc Networks are subjected to more vulnerabilities than the fixed networks as they are self-organized, self-configured, and self-controlled infrastructure-less networks. As such, in this research we are concentrating more on securing mobile ad hoc networks. Within the wireless domain, packets are forwarded to the destination usually through the intermediate nodes that act as routers. Packets are more prone to different vulnerabilities while routed from a source to a destination passing through untrustworthy intermediate nodes. A change in one bit within an incoming packet may lead to serious security preaches. In this dissertation, an immune inspired node-based distributed detection system has been implemented. The system has been analyzed, algorithms that simulate the main immune mechanisms have been mapped out, and a security framework that incorporates different immune mechanisms has been developed. The protocol has been implemented in a real wireless environment wherein the obtained results ascertain the protocol applicability. Moreover, other results have been achieved as the protocol has been simulated for benchmarking purposes. System complexity and scalability have been considered and analyzed. Although the immune-inspired security protocol (I2MANET) can be applied to many applications that rely on the wireless communications; in this dissertation, it has been specified to secure Mobile Telecommunication Services.